Going beyond galaxy ages with dense basis star formation history reconstruction. Issue Volume 15:Issue S341(2019) (November 2019) - Iyer, Kartheik G.; Gawiser, Eric
Abstract: Panchromatic SED fitting allows us to better resolve degeneracies between quantities like the star formation rate and dust. This in turn allows us to more robustly extract information about the different stellar populations that comprise a galaxy's Star Formation History (SFH). Using the Dense Basis SED fitting method (Iyer & Gawiser 2017), we reconstruct the SFHs with uncertainties for a large sample of galaxies using an atlas of SEDs corresponding to a physically motivated basis of SFHs. Using Gaussian Process Regression, we encode the parameters describing these SFHs in a functionally independent form. This give us more robust estimates for quantities like Stellar Masses and Star Formation Rates, that directly depend on the SFH. These SFHs can additionally be used to answer questions like the time at which a galaxy's star formation peaked, and how many major episodes of star formation occurred in a galaxy's past, allowing us to go beyond the traditionally estimated 'Galaxy Age', which is often poorly constrained. They also allow us to probe the high-redshift low-stellar mass regime of the SFR-M* correlation by constructing trajectories in SFR-M* space for each galaxy.